If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 3 = x + -12 Combine like terms: 9 + 3 = 12 12 = x + -12 Reorder the terms: 12 = -12 + x Solving 12 = -12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + -1x = -12 + x + -1x Combine like terms: x + -1x = 0 12 + -1x = -12 + 0 12 + -1x = -12 Add '-12' to each side of the equation. 12 + -12 + -1x = -12 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = -12 + -12 -1x = -12 + -12 Combine like terms: -12 + -12 = -24 -1x = -24 Divide each side by '-1'. x = 24 Simplifying x = 24
| (8c^2d)(6abd^2)= | | (x+1)(x-3)(x+4)=0 | | 2-6=x+8 | | -18-x=2x+21 | | (6x^3y)(-6axy)= | | 2-3y=t | | 16x^2-9y^2+64x-18y-71=0 | | 6x^2-5=-37 | | (5u-w)(3u-6w+7)= | | (-10bc^3d)(-5bcd)= | | 2(5x+3)+2(3x+4)=20x+1 | | 5(-6-3d)=3(3y-2) | | 1000(1.15/12)^12*1 | | 5x/8-3 | | 2(5x+3)+2(3x+4)=10x+1 | | (15x^3y^2)(2axy)= | | 2(m-8)=4(m+6)whatism | | (-15r^6)(-5r^3s)= | | 2(x+10)+4=6(x-10) | | x+81+88=400 | | (-16z^3)(9yz)= | | 2p+10=9+3p | | L*2=L*5-6 | | 6n^2+7=31 | | 2(6x+8)+2(8x+6)=16(4x+2) | | (4z^5)(12yz)= | | 2mr(-6mr^6)= | | 2(9x+12)+2(12x+9)=24(6x+3) | | (2xy^3)(6x^4)= | | (-6ab^2)(-9bc)= | | 23x^2-34x=0 | | (9ay)(-8y)= |